PERANAN AKUN INSTAGRAM @NSHMOUNTAINGOLD SEBAGAI MEDIA INFORMASI CLUB BASKET NSH MOUNTAIN GOLD - fauziah, Fauziah; Mantiri, Randi; Kamaruddin, Muhammad Junaid (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2024)
Social media is another form of communication which aim to promulgate informations and to communicate with many people. Social media can be used to help it users to provide informations and make better interaction with other users. Instagram is one of the example of social media platform that is rapidly grow among other platforms and currently Instagram has a high level of popularity. In the world of sports, social media is mostly used as media to give informations. This research aims to find out the role of the Instagram account of NSH Mountain Gold basketball club as a media for basketball club information. This research uses qualitative method and also use an interactive analysis model, which follows the process of data collection, data reduction, data presentation and drawing conclusions. Based on research that has been carried out using the uses and gratification theory by researchers regarding